Remember me [large type] - Balogh, Mary (Balogh, Mary. Ravenswood novel, 2023)
"Philippa grew up eagerly anticipating marriage. Then her hopes were shattered when she overheard the Marquess of Roath viciously insult her upon learning of her father's identity. Years later Duke of Wilby has tasked his grandson and heir, Lucas Arden, Marquess of Roath, with marrying and producing a son. He is instantly attracted to his sister's new friend, until that young lady asks: "Remember me?" And suddenly he does remember her. Telling Philippa the truth is the hardest thing Lucas has ever faced, and it will change them both before they discover the healing power of love"--